Musik Tradisi Talempong Batu dalam Kebudayaan - Fadhila, Natasya; Halim, M. (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Talempong is a traditional Minangkabau musical instrument, made of brass and similar in shape to the Javanese gamelangan. It is typically used to accompany traditional Minangkabau songs and dances. The aim was to gain a deeper understanding of the stone talempong and its cultural rituals. This method involved direct observation. Participants came from various backgrounds, including those from articles and lecturers. Data analysis was conducted per subject, observing the conditions in each session. The results showed that the stone talempong possesses a unique cultural identity, particularly in its rituals.